2022
DOI: 10.56556/jescae.v1i3.169
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation and Hygiene Practice among Students in Secondary School, Ijebu Ode, Nigeria

Abstract: Studies have documented that poor WaSH is accountable for several cases of diarrhea globally, resulting in millions of unnecessary deaths each year, particularly among children, and most notably in underdeveloped countries where poor knowledge and practice of WaSH have been well documented. Therefore, the work prioritizes evaluation of WaSH practice among students in secondary school in Ijebu Ode, in light of the emergence of COVID-19, which has further highlighted the essence of WaSH practice, especially in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In analyzing the handwashing practices and its predictors in primary school students of Damote Woide district in South Ethiopia, it was found that proper hand washing practices was poor (28.10%) and puts the students at risks of infections (Admasie et al, 2022). Similar observations of poor handwashing practices, inadequate handwashing facilities and education in basic schools have been recorded in other studies (Muramatsu-Noguchi et al, 2022;Sharma and Adhikari, 2022;Saima Alam et al, 2020;Okello et al, 2019;Steenkamp et al, 2022;McMichael, 2019;Otto, Opatoki and Luyi, 2022;Eshetu, Kifle and Hirigo, 2020;Toleubekov, Bolatova and Stafström, 2022) Ghana, a developing nation, was also affected by the Covid-19 pandemic. This required that schools in the country, especially at the basic level, were supplied with handwashing facilities.…”
Section: Introductionsupporting
confidence: 78%
“…In analyzing the handwashing practices and its predictors in primary school students of Damote Woide district in South Ethiopia, it was found that proper hand washing practices was poor (28.10%) and puts the students at risks of infections (Admasie et al, 2022). Similar observations of poor handwashing practices, inadequate handwashing facilities and education in basic schools have been recorded in other studies (Muramatsu-Noguchi et al, 2022;Sharma and Adhikari, 2022;Saima Alam et al, 2020;Okello et al, 2019;Steenkamp et al, 2022;McMichael, 2019;Otto, Opatoki and Luyi, 2022;Eshetu, Kifle and Hirigo, 2020;Toleubekov, Bolatova and Stafström, 2022) Ghana, a developing nation, was also affected by the Covid-19 pandemic. This required that schools in the country, especially at the basic level, were supplied with handwashing facilities.…”
Section: Introductionsupporting
confidence: 78%
“…Their responses were tabulated and the results are presented in Table 1. , 2004), creating high-risk situations where diseases can readily spread (Otto, Opatoki & Luyi, 2022). A study by Abanyie, Ampadu, Frimpong & Amuah, (2023) in Ghana found that due to availability of safe drinking water in schools, there was improvement in school attendance and performance of school children.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic will have long-term effects on the worldwide economy (Al-kasasbeh, 2022). Meanwhile, Various studies have explored factors influencing COVID-19 transmission, including air pollution (Maniat et al, 2023)and preventative measures like handwashing (Otto, Opatoki, & Luyi, 2022). An observational study in USA California, using data from the Environmental Pollution Agency (EPA), reported negative correlations between PM2.5 levels and both COVID-19 cases (-0.45) and mortality (-0.42) (Bashir, Jiang, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%